A spectrofluorimetric study of the limbal area in patients with primary open-angle glaucoma - V. V. Neroev; V. V. Gar’kavenko; V. V. Salmin (Российский офтальмологический журнал)
Purpose: to evaluate hypoxic changes in the limbus area conjunctiva of patients with primary open-angle glaucoma (POAG) treated with prolonged instillations of prostaglandin (PG) analogs. Material and methods. A spectrofluorimetric study of the limbus zone was carried out in 202 patients aged 56–87 years with POAG in the developed and advanced stages, divided into 2 groups. Group 1 consisted of patients aged 69.4 ± 10.3 years who received beta-blockers (BB) and carbonic anhydrase inhibitors (ICA) for 5–10 months; of these, 39 (30.2 %) had a developed stage of POAG and 90 (69.7 %) had advanced POAG. Group 2, aged 72.3 ± 9.4, received PG analogs, in addition to BB and ICA, for 5–10 months. In this group, 21 (28.7 %) patients had developed POAG and 52 (71.23 %) had advanced POAG. Results. The patients who received PG instillations showed a significantly higher ratio of fluorescence intensity in the wavelength range of 410/520 nm NADH/FAD (0.352 ± 0.043) than those receiving no such therapy (0.319 ± 0.047), which can be interpreted as a hypoxic state of the limbus area. Conclusion. Spectrofluorimetric testing of POAG patients taking PG analogs can be useful for detecting ischemia in the limbus area, because this category of patients are very likely to form cicatricial changes in the area of the filtration cushion in the early postoperative period after antiglaucomatous interventions.